The Experimental Garden in the E-Commerce System of the Faculty of Agriculture (KPFP) at Udayana University - Gede Mekse Korri Arisena; Dwi Putra Darmawan; A.A.A. Wulandira Sawitri Djelantik; Nyoman Tri Lukpitasari Korri; Dina Lare Dunensa; Anak Agung Keswari Krisnandika; Ni Made Classia Sukendar (Universitas Muhammadiyah Malang, 2023)
The marketing of agricultural products has long been a challenge for the Experimental Garden of the Faculty of Agriculture (KPFP), particularly in the business-to-customer (B2C) arena. To address this issue, KPFP, as one of the business units at Udayana University, has recently embarked on the development of an e-commerce system, recognizing its potential as an alternative medium for promotion, communication, and information dissemination. The objective of this study is to identify the characteristics of each KPFP field and to design an e-commerce system that caters to their respective needs. The analytical approach employed in this study was descriptive qualitative method, supported by simple tabulations and the Lean User Experience (Lean UX) approach. Our findings reveal that each KPFP field has performed its assigned tasks and responsibilities satisfactorily. The e-commerce system we have developed offers customers a choice of payment methods, including cash on delivery (COD), and ensures timely delivery, thus enabling customers to enjoy the products in a fresh condition without any loss of quality. Further research is needed to assess the system's effectiveness using the Success Rate as a usability parameter and to evaluate the efficiency of usage time, measured in seconds or minutes, required by customers to complete each task.